Teachers’ Digital Competence, Readiness and Challenges in the 21st Century Education - Baybay, Kris Kringle V.; Lantaka, Ivy A. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the level of teachers’ digital competence, readiness, and the challenges they face in delivering 21st-century education. The research was conducted among public elementary school teachers in Zamboanga City and utilized a descriptive-quantitative research design. This approach was employed to gain a deeper understanding of the experiences, perceptions, and challenges encountered by teachers in integrating technology into 21st-century education. Findings revealed that the level of teachers’ digital competence is generally rated as “Competent” in terms of device operation, internet navigation, and creating materials or lessons using digital tools. Similarly, the level of teachers’ digital readiness was rated as “Agree” in terms of access to technology, although this was influenced by factors such as unreliable internet connectivity. Respondents “Strongly Agreed” in terms of basic digital literacy, and “Agreed” regarding the use of digital tools in teaching. The study also revealed that teachers face challenges in delivering 21st-century education through the use of technology. These challenges are attributed to several factors affecting the quality of instruction, including lack of access to resources, insufficient training, and limited preparation time. Statistical analysis showed a significant difference in the level of teachers’ digital competence when grouped according to age, training, and years of teaching experience. Furthermore, teachers’ digital readiness also showed a significant difference when grouped by age and years of experience, while no significant difference was observed in terms of training. These findings suggest that while teachers are generally prepared and competent in using digital tools, there remain gaps that must be addressed through sustained professional development, improved infrastructure, and differentiated support systems. The study highlights the importance of continuous investment in teacher training and school technology resources to ensure effective implementation of 21st-century teaching practices.